Influence of the Bulk Resistivity on Silicon Heterojunction Solar Cells and Module Reliability. Issue 5 (6th January 2022) - Augusto, André; Srinivasa, Apoorva; Bowden, Stuart G.
Abstract : Recent developments in industry on surface passivation open the possibility of using less doped substrates in silicon solar cells. We investigate how the bulk resistivity affects the performance of silicon cells and the reliability of modules. Herein, n‐ and p‐type silicon heterojunction cells with bulk resistivities between 3 and 15 000 Ωcm are studied. We measure the current–voltage characteristics of n‐type cells across the resistivity range, and we find comparable responses to illumination intensities between 0.1 and 1 suns. The cells with bulk resistivities over 1000 Ωcm show breakdown voltages larger than −1000 V, almost two orders of magnitude higher than in typical commercial cells. Although modules have bypass‐diodes to prevent cells from going into breakdown, higher breakdown voltages can improve the reliability of modules in case of bypass‐diode failure and reduce the module cost by easing the number of bypass‐diodes required. Finally, the cells have been submitted to light soaking. The float‐zone p‐type cells with bulk resistivities over 10 000 Ωcm are less sensitive to light‐induced degradation than cells with bulk resistivities below 10 Ωcm. The former show to recover few hours after light soaking, while the latter recover only after dark annealing. Abstract : Silicon heterojunction cells with bulk resistivities of 15 000 Ωcm can withstand low illumination intensities and accomplish breakdown voltages over −1000 V, almost two orders of magnitude larger than most commercial cells. Higher breakdown voltages can improve the reliability of modules in case of bypass‐diode failure and reduce the module cost by easing the number of bypass‐diodes required.